A Systematic Review of Health Literacy in People Living With Parkinson's Disease - Saleha Mahomed‐Kola; Jennifer Watermeyer; Aline Ferreira‐Correia (Health Science Reports, 2026)
ABSTRACT Background and Aim Health literacy (HL) is important for People with Parkinson's Disease (PwPD), as the complexity of symptom management requires individuals to understand and apply health information across diverse healthcare contexts. This systematic review aims to provide a narrative synthesis of worldwide evidence on HL in PwPD by synthesizing overarching themes that demonstrate the ways in which HL affects disease management. Methods A narrative, thematic synthesis of the included studies was done. Articles were accessed from 13 online databases and 2 AI search engines using the keywords (“health literacy” OR “ehealth literacy” OR “education intervention” OR “knowledge” OR “training” OR “access to resources”) AND “Parkinson's Disease.” Peer‐reviewed empirical research evaluating HL in PwPD was assessed for evidence strength. Results Sixteen articles met the inclusion criteria. Four themes were identified: (1) Knowledge and understanding of Parkinson's disease; (2) Resources for building health literacy; (3) Caregiver health literacy; and (4) Access to care. Eleven studies were conducted in the Global North and five in the Global South, confirming the underrepresentation of Global South populations in HL research. Health literacy levels varied and were shaped by regional differences and information sources. Caregivers' HL affected care quality and burden, with educational programs showing potential to improve outcomes. Misconceptions persisted across regions, including beliefs in a cure and misunderstanding of symptoms. Disparities in education and access to care were tied to socioeconomic factors and hindered effective disease management. Conclusion Targeted educational interventions are necessary to correct misconceptions, promote digital health tools for self‐management, and address disparities in care. Improving HL in PwPD is key to improving their quality of life (QoL). Trial Registration: PROSPERO (CRD42024512506).